Changes to an urban marina soundscape associated with COVID-19 lockdown in Guadeloupe. (15th November 2021) - Bertucci, Frédéric; Lecchini, David; Greeven, Céline; Brooker, Rohan M.; Minier, Lana; Cordonnier, Sébastien; René-Trouillefou, Malika; Parmentier, Eric
Abstract: In 2020, the COVID-19 pandemic led to government-enforced limits on activities worldwide, causing a marked reduction of human presence in outdoors environments, including in coastal areas that normally support substantial levels of boat traffic. These restrictions provided a unique opportunity to quantify the degree to which anthropogenic noise contributes to and impacts underwater soundscapes. In Guadeloupe, French West Indies, a significantly lower number of motor boats were recorded in the vicinity of the major urban marina during the peak of the first COVID-19 lockdown (April–May 2020), compared with the number recorded post-lockdown. The resumption of human activities at the end of May was correlated with a maximum increase of 6 decibels in the ambient noise level underwater. The change in noise level did not impact daily sound production patterns of vocal fishes, with increased activity at dusk seen both during and after the lockdown period. However, during the lockdown vocal activity was comprised of a reduced number of sounds, suggesting that anthropogenic noise has the potential to interfere with vocalization behaviours in fishes. Graphical abstract: Image 1 Highlights: This study quantifies changes in underwater noise during the COVID-19 lockdown. Noise recorded near a marina of Guadeloupe was 6 dB lower during the lockdown. The number of boats was twice as high after the lockdown than during it. A lower number of sounds produced by fishes was detected during the lockdown.